Cross sectional study on analysis of reasons for refusal of PPIUCD at GIMS, Gadag - J. C., Supritha; A. K., Jayashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Women are highly motivated and receptive to accept Family Planning (FP) methods during the postpartum period. Intrauterine Contraceptive Device (IUCD) is one of the commonly used reversible methods of contraception and provide very effective, safe and long-term protection against pregnancy and the health risks associated with the method are negligible. Taking advantage of the immediate postpartum period for counselling on family planning and IUCD insertion, overcomes multiple barriers to service provision. The increased institutional deliveries are opportunity to provide women easy access to immediate PPIUCD services. Objective-The aim of the study was to determine proportion of women accepting postplacental intrauterine contraceptive device insertion, and to describe the factors associated with acceptability and non-acceptance. Methods: Cross-sectional study conducted from September 2021 to October 2021 in 250 women admitted for delivery at Gadag institute of medical sciences, Gadag. The respondents were interviewed using structured interviewer administered questionnaire. Results: In the study, it is found that overall awareness regarding PPIUCD in the study population is only 32% which is comparable with the study findings of Rajasthan where the 8 awareness was 20.2%. The readiness rate for PPIUCD insertion after the counselling in present study was 8% which is similar the study report from Government Medical College, Trissur, Kerala where the acceptance rate 1 was 10.5%. The major factors associated with nonacceptance were refusal by patient (50%) and relatives. Conclusions: The emerging factors for less acceptance of PPIUCD are low literacy rate among women and infrequent counselling and education during antenatal period. Integration of a PPIUCD counselling service at every delivery point with provision of couple counselling can improve the success of this programme.